Peningkatan Pemahaman Mahasiswa Jurusan Akuntansi Syariah tentang Teknik Penentuan Informan untuk Riset Akuntansi Budaya - Mohamad Anwar Thalib (Jurnal Pemberdayaan Ekonomi, 2022)
Purpose: This training aims to improve understanding and implementation of the use of qualitative methods focused on discussing informant determination techniques for cultural accounting research. Method: The presenters divided the training method into three parts; first, an explanation of the technique of determining informants; second, an illustration of the technique of determining informants in the type of qualitative research; third, training in informant determination techniques in the type of qualitative research for cultural accounting research. Results: The results of the first stage of the evaluation find that 10 out of 25 students majoring in Islamic accounting are interested in raising the theme of cultural accounting research; the second stage of evaluation, shows that the participants have understood the concept of informant selection techniques; the third stage evaluation resulted in participants having been able to implement the concept of informant selection techniques in the design of cultural accounting research. Conclusions: The results of the training showed that there was an increase in participants' understanding of the determination of informant techniques for cultural accounting research.